To solve the expression \( -4(3 + 12^0) + 15^0 \) using the Zero Power Rule, we must first understand that any non-zero number raised to the power of 0 equals 1 (i.e., \( a^0 = 1 \) for \( a \neq 0 \)).
-
Applying the Zero Power Rule:
- \( 12^0 = 1 \)
- \( 15^0 = 1 \)
-
Substitute those values into the expression: \[ -4(3 + 1) + 1 \]
-
Simplify:
- \( 3 + 1 = 4 \)
- \( -4(4) + 1 \)
- \( -16 + 1 = -15 \)
So, the correct process is: \[ -4(3 + 12^0) + 15^0 = -4(3 + 1) + 1 = -4 \cdot 4 + 1 = -16 + 1 = -15 \]
The response that correctly follows this process is: −4(3+12 to the power of 0)+15 to the power of 0=−4(3+1)+1=−4⋅4+1=−16+1=−15